Помехоустойчивое кодирование: различия между версиями

(+{{Википедия|Коды, исправляющие ошибки}})
 
Что можно привести к виду
 
:<math>
P_{miss}(2,n,p)&={{((1-p)+p)^n+((1-p)-p)^n -2(1-p)^n}\over 2}={{1-2(1-p)^n+(1-2p)^n}\\over 2}.
\begin{array}{l @{} l}
P_{miss}(2,n,p)&={{((1-p)+p)^n+((1-p)-p)^n -2(1-p)^n}\over 2}=\\
&={{1-2(1-p)^n+(1-2p)^n}\over 2}.
\end{array}
</math>
 
 
:<math>
&=P_{miss}(2,n,p)={1-2+(1-p2p)^n+-2(1-2pp)^n} \over 2}.,
\begin{array}{r@{}c@{}l}
</math>
P_{miss}(2,n,p)&=&{1+(1-2p)^n-2(1-p)^n \over 2},\\
 
P_{miss}(3,n,p)&=&{1+(1-p+e^{\frac{2\pi}{3}\im} p)^n+(1-p+e^{-\frac{2\pi}{3}\im} p)^n-3(1-p)^n
:<math>
\over 3},\\
P_{miss}(43,n,p)&=&{1+(1-p+e^{\frac{2\pi}{3}\mathbf{i}} p)^n+(1-p+e^{-\frac{2\pi}{3}\immathbf{i}} p)^n-3(1-p)^n\over 3},
</math>
p)^n+(1-p+e^{\frac{2\pi}{2}\im} p)^n+ (1-p+e^{\frac{3\pi}{2}\im}
 
p)^n-4(1-p)^n
:<math>
\over 4}=\\
P_{miss}(34,n,p)&=&{1+(1-p+e^{\frac{2\pi}{32}\immathbf{i}} p)^n+(1-p+e^{-\frac{2\pi}{32}\immathbf{i}} p)^n+1-p+e^{\frac{3\pi}{2}\mathbf{i}} p)^n-4(1-p)^n \over 4}=
&=&{1+(1-2p)^n + 2((1-p)^2+p^2)^{n \over
</math>
2}\cos(n\arctan{p\over (1-p)})-4(1-p)^n \over 4}.
:<math>
\end{array}
&=&{1+(1-2p)^n + 2((1-p)^2+p^2)^{n \over 2}\cos(n\arctan{p\over (1-p)})-4(1-p)^n \over 4}.
</math>
 
481

правка